The causes, effects and how to deal with cyber terrorism From an Islamic and international perspective - المدرس اىٍصاغد نارزان فلي خييو نريً (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
There is no doubt that one of the most conspicuous manifestations of terrorism in this present era is the drastic danger of terrorism in the developed world. One of the new and modern forms of terrorism is the cyber terrorism. The world is progressing and developing by means of communication and modern technology. Cyber terrorism has become a major threat to the security and stability of countries throughout the world. There is a strong link between technology, modern communications and terrorism. This link is the direct result of a gaps in information security along with the absence of social and religious enlightenments. This is a direct result of the lack of experience and the development of technologies and digital technologies on the one hand and the failure to teach the true Islam on the other. In the present era, the emergence of a new criminal world is via cyber terrorism. The easiness of using technology and facilitating communication between terrorist groups, the methods of persuasion and the development of advanced terrorist methods have even made this threat more serious regarding its danger. All of the above issues the definition of the concept of cyber terrorism, the reasons and causes of its occurrence and the remedy methods all are the focus of this research paper.